Ultrasonic assisted oil extraction and biodiesel synthesis of Spent Coffee Ground - Goh, Brandon Han Hoe; Ong, Hwai Chyuan; Chong, Cheng Tung; Chen, Wei-Hsin; Leong, Kin Yuen; Tan, Shiou Xuan; Lee, Xin Jiat (Elsevier, 2020)
Spent Coffee Ground (SCG) was studied as a potential source of oil feedstock for biodiesel production as an alternative waste utilisation instead of being disposed as municipal waste. This study evaluated the ultrasonic assisted oil extraction from SCG, which was followed by biodiesel conversion via transesterification. Hexane was found to be the most effective extractant for SCG oil. Soxhlet extraction could obtain maximum SCG oil yield of 12.5% within 3 h whereas the highest SCG oil yield (14.52%) using ultrasonic extraction was obtained at hexane to SCG ratio of 4 mL g−1 and at 30% ultrasonic amplitude for 30 min. The improved oil yield with shorter extraction time was due to the ultrasonic fragmentation on SCG cells, which enhanced the interactions between oil and solvents. Fourier transform infrared analysis showed that the SCG oil possessed suitable functional groups for biodiesel conversion. Then, the SCG oil was successfully converted to biodiesel via ultrasonic assisted transesterification. The optimal FAME yield (97.11%) was achieved with molar ratio of methanol to SCG oil of 30:1, 4 wt% of catalyst concentration, at 30% ultrasonic amplitude and for 3 h. The produced SCG biodiesel has promising properties which adhere to the biodiesel standards but acid value was beyond the permissible limit which could be overcome by utilising as blend feedstock with other commercially available biodiesel. The high calorific value along with low viscosity, density and corrosion properties suggested SCG biodiesel as an interesting and viable option for biodiesel blending. © 2019